Occupational exposure and challenges in tackling M. bovis at human–animal interface: a narrative review - Devi, K. Renuga; Lee, L. J.; Lee, Tze Yan; Amin Nordin, Syafinaz; Ismail, Rosnah; Chin, V. K. (Springer, 2021)
Zoonotic tuberculosis caused by Mycobacterium bovis (M. bovis), a member of Mycobacterium tuberculosis complex (MTBC) has increasingly gathered attention as a public health risk, particularly in developing countries with higher disease prevalence. M. bovis is capable of infecting multiple hosts encompassing a number of domestic animals, in particular cattle as well as a broad range of wildlife reservoirs. Humans are the incidental hosts of M. bovis whereby its transmission to humans is primarily through the consumption of cattle products such as unpasteurized milk or raw meat products that have been contaminated with M. bovis or the transmission could be due to close contact with infected cattle. Also, the transmission could occur through aerosol inhalation of infective droplets or infected body fluids or tissues in the presence of wound from infected animals. The zoonotic risk of M. bovis in humans exemplified by miscellaneous studies across different countries suggested the risk of occupational exposure towards M. bovis infection, especially those animal handlers that have close and unreserved contact with cattle and wildlife populations These animal handlers comprising of livestock farmers, abattoir workers, veterinarians and their assistants, hunters, wildlife workers as well as other animal handlers are at different risk of contracting M. bovis infection, depending on the nature of their jobs and how close is their interaction with infected animals. It is crucial to identify the underlying transmission risk factors and probable transmission pathways involved in the zoonotic transmission of M. bovis from animals to humans for better designation and development of specific preventive measures and guidelines that could reduce the risk of transmission and to protect these different occupational-related/populations at risk. Effective control and disease management of zoonotic tuberculosis caused by M. bovis in humans are also hindered by various challenges and factors involved at animal–human interface. A closer look into factors affecting proper disease control and management of M. bovis are therefore warranted. Hence, in this narrative review, we have gathered a number of different studies to highlight the risk of occupational exposure to M. bovis infection and addressed the limitations and challenges underlying this context. This review also shed lights on various components and approaches in tackling M. bovis infection at animal–human interface.